Characteristics of Poor Prognosis in Patients with Cerebral Venous Sinus Thrombosis: A Multicenter Retrospective Study - Zhang Y; Liu Y; Qin B; Tang S; Liang Z (Neuropsychiatric Disease and Treatment, 2023)
Yunli Zhang,1,2,* Yayuan Liu,1,3,* Bin Qin,1,4 Shiting Tang,1,5 Zhijian Liang1 1Department of Neurology, The First Affiliated Hospital of Guangxi Medical University, Nanning, People’s Republic of China; 2Department of Intensive Care Unit, The People’s Hospital of Guangxi Zhuang Autonomous Region, Nanning, People’s Republic of China; 3Department of Neurology, Minzu Hospital of Guangxi Zhuang Autonomous Region, Nanning, People’s Republic of China; 4Department of Neurology, Liuzhou People’s Hospital, Liuzhou, People’s Republic of China; 5Department of Neurology, Second Affiliated Hospital of Guangxi Medical University, Nanning, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhijian Liang, Department of Neurology, The First Affiliated Hospital of Guangxi Medical University, No.6 Shuangyong Road, Nanning, People’s Republic of China, Tel +86-771-5330705, Fax +86-771-5352627, Email liangzhijian@gxmu.edu.cnPurpose: The present study aimed to identify the characteristics, predictors, and imaging features of poor recovery in cases of cerebral venous sinus thrombosis (CVST).Patients and Methods: A total of 290 consecutive adult patients with CVST were enrolled from January 2017 to December 2021 from five hospitals in Nanning, Guangxi. According to the modified Rankin scale (mRS) score at hospital discharge, the patients were classified into good prognosis (GP, mRS ≤ 2) groups and poor prognosis (PP, mRS> 2) groups. Logistic regression was used to identify factors associated with clinical outcomes.Results: Of the 290 patients, 35 were assigned to the PP group and 255 to the GP group. No significant difference in sex was observed between the two groups. Headache (76.21%) was the most frequent symptom of CVST, and local head and neck infection was the major comorbidity (26.21%). Approximately half of the patients (48.62%) had brain injury lesions < 1 cm, and the most commonly affected sinus was the lateral sinus (81.03%). Less-common headaches (odds ratio [OR]: 2.769, p=0.046), altered mental status (OR: 0.122, p< 0.001), hematologic disorder (OR: 0.191, p=0.045), and injury to multiple lobes (OR: 0.166, p=0.041) were associated with poor clinical outcomes.Conclusion: Headache was the most common and protective manifestation of CVST, and disturbances in consciousness were an important indication of poor clinical prognosis. Patients with hematologic diseases also tended to have poor outcomes. No significant correlation was found between the number and location of venous sinus thromboses and clinical prognosis; however, intracranial injury involving multiple lobes was often associated with poor prognosis.Keywords: cerebral venous sinus thrombosis, cerebral infarction, intracranial hemorrhage, hematologic disorder, prognosis